Eksistensi Majelis Zikir Dan Pembentukan Akhlak Generasi Muda Kota Banda Aceh - Arfah Ibrahim (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
In the last decade, various groups of dhikr assemblies have emerged in Banda Aceh. The presence of the dhikr assembly has broadly attracted the interest of Banda Aceh people to join in including youth. Majoriti those who joined the assembly of zikr caused by the aridity of the soul who wants to find peace and tranquility in the remembrance of mind. Therefore, the existence of the dhikr assembly in Banda Aceh is accepted by most layers of society. Nevertheless, in the last year, the call to remembrance has been massively no longer vibrant when compared to a few years ago. This raises the perception that dhikr made during this time is closely related to the political season and is full of political interests from certain groups. Nevertheless, this article concludes that the existence of the assembly of remembrance needs to be maintained by the people of Aceh because the assembly of remembrance becomes a means that can bring society closer to Allah SWT, helping to shape the morality of the younger generation, thus changing their attitude to become a better person as a servant of God and also as social beings